2022
DOI: 10.3390/ma15103733
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Independent Metamaterial Absorber with Anti-Reflection Coating Nanoarchitectonics for Visible and Infrared Window Applications

Abstract: The visible and infrared wavelengths are the most frequently used electromagnetic (EM) waves in the frequency spectrum; able to penetrate the atmosphere and reach Earth’s surface. These wavelengths have attracted much attention in solar energy harvesting; thermography; and infrared imaging applications for the detection of electrical failures; faults; or thermal leakage hot spots and inspection of tapped live energized components. This paper presents a numerical analysis of a compact cubic cross-shaped four-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Longer wavelengths can penetrate larger cover layers, however, this increases by 850–2000 nm absorption. Similar absorption characteristics of various thickness layers in metamaterial absorbers in the optical region are described by Ahmed Musa et al 39 After evaluating the impact of various cover layer H up thicknesses, H up = 10 nm is considered for confirming the proposed meta-structure unit cell design. Hence, it can be said that the cover layer acts as an anti-reflection surface.…”
Section: Design Methodologymentioning
confidence: 84%
See 3 more Smart Citations
“…Longer wavelengths can penetrate larger cover layers, however, this increases by 850–2000 nm absorption. Similar absorption characteristics of various thickness layers in metamaterial absorbers in the optical region are described by Ahmed Musa et al 39 After evaluating the impact of various cover layer H up thicknesses, H up = 10 nm is considered for confirming the proposed meta-structure unit cell design. Hence, it can be said that the cover layer acts as an anti-reflection surface.…”
Section: Design Methodologymentioning
confidence: 84%
“…Here, the dimensions of the proposed meta-structure are taken according to recent research in optical wavelength applications. 36,39,52,[64][65][66][67][68] The unit cell's resonator metal layer is composed of four linked cylinders, each connected to a T-shaped Jerusalem cross. The proposed meta-structure unit cell geometry is finalized in five steps, as shown in Fig.…”
Section: Design Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Prashant et al introduced a uniformly arranged array of gold nanotubes on top of the ITO anti-reflection film and found that it could effectively increase the light trapping in the visible and infrared waveband after applying Finite-Difference Time-Domain analysis [16]. Musa et al used a metal-dielectric-metal-dielectric structure to design a SiO 2 -based intercalated tungsten ARL that can be used in the 350-1350 nm waveband, improving the average absorption of the material in the visible and infrared wavebands [17]. Wang M. et al proposed a ZnO nano-pin array structure constructed on the textured polycrystalline silicon surface, which reduced the reflection in the visible-NIR band and enabled the cell to exhibit excellent light trapping performance in the 350-1100 nm waveband [18].…”
Section: Introductionmentioning
confidence: 99%